Release, establishment, spread, and impact of the weevil Neohydronomus affinis (Coleoptera: Curculionidae) on water lettuce (Pistia stratiotes) in Benin, West Africa - Ajuonu, O.; Neuenschwander, Peter (2003)
The weevil Neohydronomus affinis Hustache (Coleoptera : Curculionidae) of Neotropical origin was imported into Benin in 1993 and released in 1995 for the biological control of water lettuce Pistia stratiotes L. (Araceae). After the release of N. affinis in water bodies linked to the Mono River system, southwestern Benin, larval mines characteristic of immature stages were observed in all seasons in the first year and the weevil was considered established. Two years later, it had spread 90 km from the release site to the Ouémé River, and by 2000 to Savalou, which is 250 km to the northwest. It also established in the north, in the watershed of the Niger River. At the two sites monitored, total plant biomass and weed cover fluctuated with seasonal factors but declined about ten-fold, which indicated successful biological control of water lettuce by the weevil.